Demographic and migration processes in the Far East of Russia (on the example of Primorsky Krai) - K. N. Serdyukov (Вестник университета)
This article highlights the features of demographic and migration processes characteristic of the Far Eastern Federal District (hereinafter referred to as FEFD) in general and Primorsky Krai in particular. Based on materials of official statistics, the resident population dynamics of all Russia’s subjects that are part of the FEFD is considered. In this region, the development specifics’ of modern period migration processes are revealed; differentiated indicators of migration increase/decrease in the population are analyzed. A number of implemented state initiatives are outlined, to some extent contributing to the improvement of the socio-economic situation of the FEFD, as well as the normalization of its demographic situation. However, it is noted that despite the adoption of special measures/conditions, it is not possible to overcome the negative demographic trend of the macroregion. The paper emphasizes that in the Far East external labor migration has become a valuable source of compensation for the shortage of local labor resources. Thus, according to the author, the foreign labor force of this macroregion should be considered as the most important element of its socio-economic development, putting forward the problems of international labor migration among the most priority issues.